Fundamentals of Islamic money and capital markets - Omar, Azmi.; Abduh, Muhamad; Sukmana, Raditya (Singapore : John Wiley, 2013)
The first comprehensive guide to Islamic financial markets Based on the course taught at the International Islamic University Malaysia, this is the first book on Islamic finance to focus exclusively on money and capital markets. Covering basic concepts as well as current practices in Islamic financial markets, the book features case studies from real markets. It outlines the theory of money in terms of value, supply, and demand, while explaining the Islamic capital markets in terms of classifications, types of operations, valuations of securities, Islamic unit trust, ETFs, Islamic sto.
An Introduction to Conventional and Islamic Financial Systems -- Development of Islamic Capital and Money Markets in Malaysia -- Regulators and Transactions Platform for Capital and Money Markets -- Islamic Money Market -- An Overview of Sukuk -- Shariah-Compliant Equity -- Islamic Mutual Funds -- Islamic Real Estate Investment Trusts (I-REITs) -- Islamic Exchange-Traded Funds -- Islamic Derivatives Market.
Includes bibliographical references and index.
Print version record.
Keywords: Money market -- Islamic countries; Capital market -- Islamic countries; Economics -- Religious aspects -- Islam; Islam -- Economic aspects; Capital market -- Islamic countries; Economics -- Religious aspects -- Islam; Islam -- Economic aspects; Money market -- Islamic countries; BUSINESS & ECONOMICS -- Finance; Capital market; Economics -- Religious aspects -- Islam; Islam -- Economic aspects; Money market; Islamic countries; Electronic books